(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
New challenges of the contemporary social growth paradigm shape the need for a renewed vision for socio-economic change based on an inclusive approach. The article assesses the level and dynamics of inclusive development of Ukrainian regions. Considering this, the analysis of the inclusive development of the regions becomes especially relevant for the needs of socio-economic growth in Ukraine. The purpose of the article is to evaluate the level and dynamics of inclusive development of Ukrainian regions. As a result of the research, the scientific and methodological approach to the analysis of the regional inclusive development trends in the conditions of financial decentralization was further developed. The article substantiates the need for in-depth study of the regional development, taking into account its inclusivity, which expands the analysis of economic shifts, supplementing it with indicators of the even distribution of the benefits received and assessing the possibilities of inclusion of all population segments in the processes of socio-economic growth. In accordance with the new requirements, an analysis of the inclusive regional development was conducted according to three components (economic, social and infrastructural), which allow a sufficient objective assessment of its level. The calculation of the integral index, as well as the indicators characterizing the dynamics of economic, social and infrastructural spheres, allowed to identify trends of inclusive development of the Ukrainian regions and to reveal the presence of significant interregional asymmetry.The results of the conducted research can be used in the activity of local and regional financial authorities in the system of executive power.